(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The fundamental objective of this research is to examine the manufacture of concrete pavement with a high performance by utilizing Samawa dolomite stone as a partial substitution to coarse aggregate (gravel). In this study, five mixes of concrete pavement were made containing Samwah stone as a coarse aggregate with the replacement percentage of (0%, 10%, 20%, 30% & 40%) from gravel at level of strength type C30 (the requirement of concrete pavement). Fresh concrete mixes were subjected to slump test. Compressive strength, flexural strength, static modulus of elasticity was investigated for hardened concrete mixes at age of 28 days. Test results revealed that the inclusion of locally dolomite stone as a replacement to gravel in produced concrete pavement improves the hardened properties especially for flexural strength without any significant effect on workability requirement except at replacement percentage (40% of coarse aggregate). The best performance of produced concrete pavement was adopted with replacement percentage (30%) from gravel by using locally dolomite stone.